2015
DOI: 10.1002/2015jd023260
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the connection between boreal winter ENSO and the South Asian high in the following summer by the stratospheric quasi‐biennial oscillation

Abstract: This study investigated the modulation effect of boreal winter quasi-biennial oscillation (QBO) on the connection between winter El Niño-Southern Oscillation (ENSO) events and the variability of the following summer's South Asian high (SAH) by using European Centre for Medium-Range Weather Forecasts Interim Reanalysis data for the period of 1979-2013. The results suggest that the boreal summer SAH is more significantly influenced by preceding ENSO events in the easterly phase of the QBO than in the westerly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 69 publications
(120 reference statements)
0
25
0
Order By: Relevance
“…In the tropics, El Niño-Southern Oscillation (ENSO) is the strongest air-sea interaction system, which can exert substantial influences on the global climate and weather variability (e.g., Alexander 1992;Lau and Nath 1996;Zhang et al 1997;Alexander et al 2002;Wu et al 2003Wu et al , 2010Huang et al 2004;Yu and Zwiers 2007;Feng et al 2011;Yeh et al 2011;Zhou et al 2013;Xue et al 2015). Previous studies indicated that atmospheric circulation changes and associated sea surface Abstract This study examines the influence of boreal spring Arctic Oscillation (AO) on the subsequent winter El Niño-Southern Oscillation (ENSO) using 15 climate model outputs from the Coupled Model Intercomparison Project Phase 5 (CMIP5).…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics, El Niño-Southern Oscillation (ENSO) is the strongest air-sea interaction system, which can exert substantial influences on the global climate and weather variability (e.g., Alexander 1992;Lau and Nath 1996;Zhang et al 1997;Alexander et al 2002;Wu et al 2003Wu et al , 2010Huang et al 2004;Yu and Zwiers 2007;Feng et al 2011;Yeh et al 2011;Zhou et al 2013;Xue et al 2015). Previous studies indicated that atmospheric circulation changes and associated sea surface Abstract This study examines the influence of boreal spring Arctic Oscillation (AO) on the subsequent winter El Niño-Southern Oscillation (ENSO) using 15 climate model outputs from the Coupled Model Intercomparison Project Phase 5 (CMIP5).…”
Section: Introductionmentioning
confidence: 99%
“…For example, elevated diabatic heating over the TP and latent heating associated with neighbouring summer monsoons are considered as the two main influencing factors for the variation of the SAH (Flohn, 1960; Mason and Anderson, 1963; Krishnamurti et al ., 1973; Krishnamurti and Bhalme, 1976; Reiter and Gao, 1982; Yanai et al ., 1992; Hoskins and Rodwell, 1995; Wu et al ., 1997; Ye and Wu, 1998; Liu et al ., 2004; Boos and Kuang, 2010; Ren et al ., 2019; Wei et al ., 2019; Cen et al ., 2020). In addition, sea surface temperature (SST) anomalies in the tropical Indian Ocean (TIO) plays a pivotal role in SAH variations, which has also attracted considerable attention because it serves as a significant energy source for East Asian summer monsoon variation (Zhang et al ., 2000; Yang et al ., 2007; Huang et al ., 2011; Qu and Huang, 2012; Xue et al ., 2015, 2017, 2018). Multiple time‐scale variabilities (including interdecadal, interannual, and sub‐seasonal time scales) can be clearly observed in the intensity and location of the SAH (Krishnamurti et al ., 1973; Krishnamurti and Bhalme, 1976; Zhang et al ., 2005; Zhao et al ., 2009; Qu and Huang, 2012; Wei et al ., 2012; Qu et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the major components of the Asian summer monsoon (ASM) system [3,4]. Previous studies have revealed that the SAH plays an important role in the ASM onset, active and break, and in the monsoon rainfall variability on different time scales during boreal summer [5][6][7][8][9][10][11][12][13][14][15][16][17]. The Easterly jet stream on the Southern flank of the SAH is a key factor affecting the Indian summer monsoon (ISM) onset and rainfall variability [1,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%